Physicochemical Study of Photocatalytic Activity of TiO2 Supported Palygorskite Clay Mineral - Lahcen Bouna; Benaissa Rhouta; Francis Maury (International Journal of Photoenergy)
This study deals with the influence of physicochemical parameters, namely, the photocatalyst loading, dye concentration, and pH of polluted solutions, on the degradation efficiency of Orange G (OG) solutions containing TiO2 nanoparticles supported on palygorskite clay mineral (TiO2-Pal). The TiO2 photocatalyst attached to natural palygorskite fibers was elaborated by colloidal sol-gel route. It exhibits the anatase structure that is the most photoactive crystallographic form. The highest performances of supported photocatalyst on OG degradation were found using an optimum amount of TiO2-Pal around 0.8 g·L−1, which corresponds properly to ca. 0.4 g·L−1 of TiO2. This amount is interestingly lower than the 2.5 g·L−1 generally reported when using pure unsupported TiO2 powder. The photodegradation rate increases by decreasing OG initial concentration, and it was found significantly higher when the OG solution is either acidic (pH<4) or basic (pH≈11). For OG concentrations in the range 5×10-6– 5×10-4 M, the kinetic law of the OG degradation in presence of TiO2-Pal is similar to that reported for unsupported TiO2 nanopowder. It follows a Langmuir-Hinshelwood model with a first-order reaction and an apparent rate constant of about 2.9×10-2 min−1.